Probabilistic seismic hazard assessment for Taiwan - Wang, Yu-Ju (2019)
The Taiwan Earthquake Model (TEM) was established to assess the seismic hazard and risk for Taiwan by considering the social and economic impacts of various components from geology, seismology, and engineering. This paper gives the first version of TEM probabilistic seismic hazard analysis for Taiwan in these aspects. We named it TEM PSHA2015. The model adopts the source parameters of 38 seismogenic structures identified by TEM geologists. In addition to specific fault source-based categorization, seismic activities are categorized as shallow, subduction intraplate, and subduction interplate events. To evaluate the potential ground-shaking resulting from each seismic source, the corresponding ground-motion prediction equations for crustal and subduction earthquakes are adopted. The highest hazard probability is evaluated to be in Southwestern Taiwan and the Longitudinal Valley of Eastern Taiwan. Among the special municipalities in the highly populated Western Taiwan region, Taichung, Tainan, and New Taipei City are evaluated to have the highest hazard. Tainan has the highest seismic hazard for peak ground acceleration in the model based on TEM fault parameters. In terms of pseudo-spectral acceleration, Tainan has higher hazard over short spectral periods, whereas Taichung has higher hazard over long spectral periods. The analysis indicates the importance of earthquake-resistant designs for low-rise buildings in Tainan and high-rise buildings in Taichung.